Loyalty of consumers in the retail market of women’s clothing and shoes based on satisfaction with qualitative attributes - Alves, Lilian; Moyano, Carlos Alberto Mello; Angnes, Derli Luís (Revista de Administração da UFSM, 2020)
Purpose: There are few studies about satisfaction with qualitative attributes and their factors which women look for when shopping for clothes and female shoes in the Brazilian retail market, and that is the main objective of this study, which consists in identifying the qualitative attributes that promote the service quality factors perceived by consumers in the retail market of women’s clothing and shoes in order to obtain a higher satisfaction and fidelity for this segment. Design: The methodology used was subdivided into two stages: an exploratory qualitative stage and another stage using a descriptive qualitative research with 240 female consumers in the retail market of clothes and shoes. Findings: The results of this study show a positive correlation between satisfaction and the intention of repurchasing. Four main factors were identified using a Factorial Analysis: Attending, products, service and infrastructure. Research limitations: Study was limited to women in clothing and shoes retail in only one city. Practical implications: Based on the results it was possible to establish a competitive position of the retail sector for the target market and strategy actions for improvement and to increase loyalty among the female consumers to the stores. Social implications: Reduction of consumer dissatisfaction in the retail of women’s clothing and shoes. Originality/value: Academic contributions to broaden the understanding of women’s shopping behavior in the retail market of shoes and clothes based on the identification of important attributes and factors for service quality.